A new species of Edrabius Fauvel (Coleoptera, Staphylinidae, Staphylininae) from Uruguay - Martínez-Villar, Mauro; González-Vainer, Patricia; Tomasco, Ivanna H. (Zootaxa, 2020)
A new rove beetle species, Edrabius uruguayensis Martínez-Villar, González-Vainer & Tomasco, sp. nov., associated with the subterranean rodent Ctenomys rionegrensis in Uruguay, is described and illustrated. Photographs, scanning electron micrographs and drawings of the diagnostic character states are provided. The new species is compared with other species of the genus. Nucleotide sequence of the cytochrome oxidase subunit I was reported for the first time for the genus and phylogenetic reconstruction confirms their close relationship with the other genus used from the tribe Amblyopinini (Heterothops).